2012
DOI: 10.1007/s00520-012-1545-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the social impact of cancer: a review of available tools

Abstract: The great interest in this subject as borne out by the amount of studies published in international psycho-oncological literature confirms the importance of having a valid and reliable instrument specifically dedicated to measuring the social impact of the oncological experience. At the same time, further investigation is required to investigate the psychometric properties of the existing tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…A previous systematic review by Muzzati and Annunziata [8] showed that some PROMs examine different and limited aspects of patients’ social well-being. For example the subscale of the EORTC QLQ-C30 refers to social and role functioning, the FACT-G to relatives and relationships and the Psychological Screen for Cancer [9] to social support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous systematic review by Muzzati and Annunziata [8] showed that some PROMs examine different and limited aspects of patients’ social well-being. For example the subscale of the EORTC QLQ-C30 refers to social and role functioning, the FACT-G to relatives and relationships and the Psychological Screen for Cancer [9] to social support.…”
Section: Introductionmentioning
confidence: 99%
“…For example the subscale of the EORTC QLQ-C30 refers to social and role functioning, the FACT-G to relatives and relationships and the Psychological Screen for Cancer [9] to social support. The authors of this previous systematic review [8] commented that none of the multidimensional HRQoL instruments totally captured the complexity of ‘social impact’. This led them to a systematic search of instruments dedicated solely to the assessment of the social aspects of the cancer experience (or validated in cancer populations) which yielded 27 articles relating to 14 instruments.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of cancer QOL measurements have been developed to evaluate the social component of the cancer experience; however, the items used to evaluate social problems tend to be limited, and content varies across instruments . The Social Difficulties Inventory (SDI) is 1 of the most elaborately developed standardized questionnaires that comprehensively cover the social problems experienced by cancer patients in the United Kingdom .…”
Section: Introductionmentioning
confidence: 99%
“…The Social Difficulties Inventory (SDI) is 1 of the most elaborately developed standardized questionnaires that comprehensively cover the social problems experienced by cancer patients in the United Kingdom . Nevertheless, cross‐cultural or national application of SDI may be difficult because social problems reflect factors in the social environment, such as perceptions and emotions about cancer, health‐care systems, and social welfare policies . The literature on the need for help with social problems among cancer patients is also limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation